2015
DOI: 10.1016/j.forpol.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Social capital in small-scale forestry: A local case study in Southern Sweden

Abstract: Small-scale forestry builds upon interactions among local stakeholders. Forest management entails multiple social situations such as consultations or cooperative engagements between owners and forest professionals. Successful social endeavours rest on positive social capital as operationalised via trust. Based on qualitative in-depth interviews with forest owners, managers and other forestry stakeholders, this study explores how trust influences the social relationships in a local context of Southern Swedish f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…The similarity in tribe, religion and family relationships that exist in Sidodadi and Sumur Kumbang communities strengthen the trust in the community, as bonding in social capital. Bonding social capital is presented as trust among closer and exclusive networks where members know each other very well (Guillen et al 2015). With strong bonding, communities become more open to communicate and coordinate to manage the land in forest areas.…”
Section: Trust and Collective Action In Agroforestry Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The similarity in tribe, religion and family relationships that exist in Sidodadi and Sumur Kumbang communities strengthen the trust in the community, as bonding in social capital. Bonding social capital is presented as trust among closer and exclusive networks where members know each other very well (Guillen et al 2015). With strong bonding, communities become more open to communicate and coordinate to manage the land in forest areas.…”
Section: Trust and Collective Action In Agroforestry Developmentmentioning
confidence: 99%
“…Fisher (2013) points out that trust becomes an important catalyst that allows passive information to be transformed into valuable knowledge. The idea is supported by Guillen et al (2015) who argued the importance of personal relationships and the catalyst role of social capital ties in forest management. Koutsou et al (2014) showed farmers' trust tend to increase at individual level, particularly for farmers who take collective action as well as allowing farmers to be flexible in adapting to new conditions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Roslinda (2018) considers in its work "Social Community Capital" in the management of the Danau National Park running National Park Management Center, and proved that government and the community need to cooperate and pay greater attention to resistance to changes. In a study by Swiss scientists, Guillén et al (2015) it is highlighted how trust influences social relations in the local forestry context and reveals differences in the activities of similar farms. Afandi et al (2017) consider the relationship between social capital and people's entrepreneurial participation in 35 countries in Europe and Asia and examine the impact of the three-dimensional concept of social capitaltrust, networks and norms -on the three stages of the entrepreneurial process -preference, trial and success.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nesse sentido, a importância da ARS está na conectividade dos atores sociais que são atuantes na gestão ambiental. Em geral, o capital social é baseado nos níveis de confiança, regras e combinados dentro de uma rede (BATT, 2008;BOURDIEU, 1980;BURT, 1997BURT, , 2000COLEMAN, 1988;GUILLÉN;WALLIN;BRUKAS, 2015;MARTELETO, 2004;PRETTY;WARD, 2001). A presença dessas regras é o que permite a institucionalização da rede, e o capital social pode ser entendido como um conjunto de redes e normas que reduzem os riscos de relações entre pessoas desconhecidas (SILVA;…”
Section: -------------------unclassified